Cation–π interaction in DOPA-deficient mussel adhesive protein mfp-1. Issue 5 (7th January 2015) - Kim, Sangsik; Faghihnejad, Ali; Lee, Yongjin; Jho, YongSeok; Zeng, Hongbo; Hwang, Dong Soo
Abstract : Deployment of cation–π interactions can be a complementary strategy for the successful underwater adhesion of mussels. Abstract : Here we report the possible contribution of cation–π interaction to underwater adhesion of mussels by using DOPA-deficient recombinant mussel adhesive proteins. Considering the instability of DOPA in an oxidative environment, the cation–π interaction in DOPA-deficient biopolymers provides a complementary cross-linking mechanism for the design of novel underwater adhesives.